2023
DOI: 10.1097/md.0000000000033811
|View full text |Cite
|
Sign up to set email alerts
|

Association of neutrophil-to-lymphocyte ratio with clinical, pathological, radiological, laboratory features and disease outcomes of invasive breast cancer patients: A retrospective observational cohort study

Abstract: Inflammatory conditions play part in the progression of malignancies, and markers signifying growth of these factors can indicate prognosis. Neutrophil-to-lymphocyte (NLR) is used as a marker of subclinical inflammation that may become an integral part of workup to indicate prognosis and associated pathology. This study aims to explore the association of NLR ratio with clinical characteristics, radiological assessment and staging, histopathology, and disease outcomes of breast cancer. A retrospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…NLR was examined in sickle cell anemia and was found to be high with proteinuria and positively correlated with fibrinogen levels [ 29 ]. Furthermore, NLR and anemia were independent risk factors for mortality in breast cancer patients [ 30 ]. Elevated NLR combined with decreased Hb predicted the onset of major adverse cardiovascular events in patients with ST-elevation myocardial infarction [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLR was examined in sickle cell anemia and was found to be high with proteinuria and positively correlated with fibrinogen levels [ 29 ]. Furthermore, NLR and anemia were independent risk factors for mortality in breast cancer patients [ 30 ]. Elevated NLR combined with decreased Hb predicted the onset of major adverse cardiovascular events in patients with ST-elevation myocardial infarction [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that many types of malignant neoplasms play an important role in the carcinogenic process and survival with respect to systemic inflammation [6][7][8][9][10][11][12][13][14][15][16]24]. Tumor cells themselves release cytokines and chemokines, which are thought to circulate and induce a systemic inflammatory response [25], resulting in changes in neutrophils, lymphocytes, and platelets [26].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets have been shown to protect tumor cells from adhering to and being excluded from the vascular endothelium, thus contributing to their survival and spread [29,30]. In fact, inflammatory markers have been reported to be associated with tumor stage and grade, oncological outcome, and prognosis in various types of malignant neoplasms [5][6][7][8][9][10]. Because neutrophils, lymphocytes, and platelets have these functions with respect to tumor cells, the role of the inflammation-related parameters in PCa is of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation